Clinical outcomes in COVID-19 among patients with hypertension in the Philippine CORONA Study - Adrian I. Espiritu; Ma. Sergia Fatima P. Sucaldito; Deborah Ignacia D. Ona; Almira Doreen Abigail O. Apor; Marie Charmaine C. Sy; Veeda Michelle M. Anlacan; Roland Dominic G. Jamora (European Journal of Medical Research, 2023)
Abstract Objective To describe the association between hypertension and clinical outcomes in a cohort of patients with coronavirus disease 2019 (COVID-19). Design Retrospective cohort study. Setting Thirty-seven (37) hospitals in the Philippines. Patients 10,881 patients admitted for COVID-19 from February to December 2020. Measurements and main results Among the 10,881 patients included in the Philippine CORONA Study, 3647 (33.5%) had hypertension. On regression analysis adjusted for confounders (age group, sex, smoking history, diabetes, chronic cardiac disease, chronic kidney disease, chronic respiratory disease, chronic neurologic disease, chronic liver disease, HIV/AIDS, and malignancy), patients with hypertension had significantly greater odds of in-hospital mortality (OR 1.33, 95% CI 1.17–1.52), respiratory failure (OR 1.99, 95% CI 1.75–2.28), ICU admission (OR 2.16, 95% CI 1.90–2.45) and severe/critical disease (OR 1.57, 95% CI 1.41–1.75), compared to patients without hypertension. The time-to-event analysis with confounder adjustment also showed that hypertension was significantly associated with shorter time-to-event outcomes of in-hospital mortality (HR 1.13, 95% CI 1.01–1.26), respiratory failure (HR 1.86, 95% CI 1.65–2.10), and ICU admission (HR 1.99, 95% CI 1.76–2.23). Conclusions Our analysis of nationwide data confirmed previous findings that hypertension is an independent risk factor for worse clinical outcomes among patients hospitalized for COVID-19, with increased odds of in-hospital mortality, respiratory failure, ICU admission, and severe/critical COVID-19. More specific studies should be done to elucidate the impact of hypertension characteristics, such as chronicity, severity, drug therapy, and level of control on these clinical outcomes.